Estudo Farmacológico Via Progressão Geométrica e Conjuntos Fuzzy no Ensino Médio - Silva, Graciela Nunes da (2024)
Currently, we seek to motivate students with new methodological practices for teaching mathematics. To this end, the objective of this work is to present a proposal for teaching Geometric Progression (GP), based on the concept of half-life of medicines. This mathematical modeling is carried out through the risk of intoxication of the human body by drugs, building a Fuzzy Rule-Based System (FRBS), which depends on the quantities of drugs and the elimination of drugs by the body, using the free software FisPro. In this didactic sequence, students are encouraged to be interactive in developing their knowledge, through the creation of an e-book, to give meaning to concepts and technical terms related to drugs and pharmacokinetics. A prototype of the human organism is built to indicate possible risks of poisoning, in which students interact with the FRBS using a smartphone. The potential risk of poisoning is indicated by colored lights inserted into the abdomen of the prototype, according to the FRBS output values. The manual for the construction of the prototype of this organism and entitled: Manual for the construction of the prototype of the human organism with fuzzy control is made available. Learning assessment is carried out continuously through the activities proposed during the process and quantitatively through a game created on the kahoot platform.